Empowering Adolescents to Transform Schools: Lessons from a Behavioral Targeting - Alan, Sule; Kubilay, Elif (American Economic Review, 2025)
We test the effectiveness of a behavioral program grounded in the idea that status granting and self-persuasion might yield a robust behavioral change in disadvantaged adolescents. We enlist socially connected senior middle school students with high emotional intelligence as “student-teachers” and entrust them with delivering a curriculum to their junior peers. The program empowers student-teachers, leading them to improve their social environment. It reduces disciplinary incidents and antisocial behavior among student-teachers and their friendship networks. The intervention significantly enhances the likelihood of admission to selective high schools for student-teachers, offering a cost-effective way to help disadvantaged adolescents escape neighborhood disadvantages. (JEL H52, I21, I24, I28, J13, O15)